Notes of statement by Sir William Beveridge to General Council at their meeting on 16 December, 1942 - Beveridge, William Henry Beveridge, Baron, 1879-1963
1942-12-17 1942 1940s 9 pages PRIVATE & CONFIDENTIAL. TRADES UNION CONGRESS. NOTES OF STATEMENT BY SIR WILLIAM BEVERIDGE TO GENERAL COUNCIL AT THEIR MEETING ON WEDNESDAY, 16TH DECEMBER, 1942. Miss Loughlin welcomed Sir William and Lady Beveridge and thanked them for giving up their valuable time in coming to the meeting. She said the Council wanted to wish them both very much happiness. Sir William Beveridge thanked the Council for their kind reception. He said he would not make a long statement because he hoped some members of the Council had had a chance of reading the report and would have questions to put, and he wanted to leave time for that. He pointed out that as he had another meeting that afternoon he wanted to get away from the General Council meeting by 1 o'clock. He said that one of the earliest memos. the Committee had received on Social Insurance was from the Trades Union Congress. If they looked at what they had recommended they would see that with the exception of one point there was very little difference between his proposals and the proposals of the T.U.C. He had gone in for a comprehensive scheme, for a scheme which gave uniform benefits for unemployment, disability, sickness and old age. The insured person would pay about 25%, the other 75% would come from the employer and the State, very much on the lines of the T.U.C. recommendation. He had gone in for a comprehensive medical service giving treatment to everybody. He had made the unemployment and disability benefit last as long as it need last without a means test. There again the T.U.C. proposals had been adopted, not because they had been suggested by the T.U.C., but because he thought they were right. He pointed out that he could make much the same statement to the Shipping Federation. 292/150.5/5/2